Analisis Sumber dan Penggunaan Modal Kerja Pada Koperasi Karyawan PT. Perkebunan Nusantara (PTPN) VII Bengkulu - Annisa Rahma Putri; Abdul Rahman (Universitas 45 Surabaya, 2025)
. The purpose of this study was to determine the source and use of working capital for the Ruwa Jurai Employee Cooperative of the Padang Pelawi Business Group PT. Perkebunan Nusantara VII Bengkulu. Data collection methods used are documentation and interviews, data collection documentation in the form of financial reports obtained from documents and records and records relating to working capital, as well as conducting interviews related to research on the source and use of working capital to Cooperative management Employees of Ruwa Jurai Padang Pelawi Business Group PT. Perkebunan Nusantara VII Bengkulu The results of the study are known about the source and use of working capital at the Ruwa Jurai Employee Cooperative of the Padang Pelawi Business Group PT. Perkebunan Nusantara VII. In 2020 showed an increase in working capital of Rp.962,531,524, - which is the difference from the source of working capital Rp.1,192,849,864, and the use of working capital Rp.230,318,340. 2021 showed a decrease in working capital of Rp.61,802,878. - which is the difference from the source of working capital Rp.90,441,490, and the amount of working capital use of Rp.152,244,368. In 2022 there was an increase in working capital of Rp. 437,195,081., - which is the difference from the working capital source of Rp. 487,171,557 and total working capital usage of Rp. 49,976,476 .- 2023 showed an increase in working capital by Rp. 228,546,596., - which is the difference from the source of working capital in the amount of Rp. 447,552,049, - and the total use of working capital is Rp. 248,869,281, - The largest increase in working capital was in 2020 amounting to Rp. 962,531,524, - which was caused by the withdrawal of other assets amounting to Rp.1,141,527,310. In 2021 there was a decrease in working capital by Rp.61,802,878, - after that in 2022 and 2023 there was an increase in working capital again.